Thymosin β4 limits inflammation through autophagy. (31st May 2018) - Renga, Giorgia; Oikonomou, Vasilis; Stincardini, Claudia; Pariano, Marilena; Borghi, Monica; Costantini, Claudio; Bartoli, Andrea; Garaci, Enrico; Goldstein, Allan L.; Romani, Luigina
ABSTRACT: Introduction : Thymosin β4 (Tβ4) is a thymic hormone with multiple and different intracellular and extracellular activities affecting wound healing, inflammation, fibrosis and tissue regeneration. As the failure to resolve inflammation leads to uncontrolled inflammatory pathology which underlies many chronic diseases, the endogenous pathway through which Tβ4 may promote inflammation resolution becomes of great interest. In this review, we discuss data highlighting the efficacy of Tβ4 in resolving inflammation by restoring autophagy. Areas covered : The authors provide an overview of the Tβ4's anti-inflammatory properties in several pathologies and provide preliminary evidence on the ability of Tβ4 to resolve inflammation via the promotion of non-canonical autophagy associated with the activation of the DAP kinase anti-inflammatory function. Expert opinion : Based on its multitasking activity in various animal studies, including tissue repair and prevention of chronic inflammation, Tβ4 may represent a potential, novel treatment for inflammatory diseases associated with defective autophagy.